2017
DOI: 10.1093/ejcts/ezx432
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of external venous supports in coronary artery bypass graft surgery†

Abstract: Despite the apparent superiority of arterial conduits for coronary artery bypass grafting (CABG), the long saphenous vein remains the most commonly used graft. The high failure rate of long saphenous vein grafts (SVGs) over time is therefore an important limiting factor for the long-term outcomes of CABG. Various methods to improve SVG patency have been proposed, although few have had a significant impact on clinical practice. External SVG supports have been a focus of research over the past 50 years, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…A number of mechanisms have been identified that are suggested to explain the superior performance of SVs harvested by the NT technique [60] . Most mechanisms are related to preservation of the outer cushion of fat of the SV acting as 'natural support' and therefore sharing the same beneficial properties as those proposed for the various external stents described in the recent review by Mawhinney, Mounsey, and Taggart [58] , as seen in Figure 4 from Rueda et al, 2008 [36] , and Mawhinney et al, 2017 [58] .…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…A number of mechanisms have been identified that are suggested to explain the superior performance of SVs harvested by the NT technique [60] . Most mechanisms are related to preservation of the outer cushion of fat of the SV acting as 'natural support' and therefore sharing the same beneficial properties as those proposed for the various external stents described in the recent review by Mawhinney, Mounsey, and Taggart [58] , as seen in Figure 4 from Rueda et al, 2008 [36] , and Mawhinney et al, 2017 [58] .…”
mentioning
confidence: 86%
“…outermost tissue removed (Rueda et al [36] , 2008). Insert, examples of DacronTM 'EXTENT' and 'VEST' external supports (Mawhinney et al [58] , 2017). B) An example of a no-touch (NT) harvested SV with external tissue intact (Rueda et al [36] , 2008).…”
Section: Fig 4 -Unsupported and Supported Saphenous Vein (Sv) Graftsmentioning
confidence: 99%
See 3 more Smart Citations